The effect of perceived usefulness, perceived risk and offline consultation habit on telemedicine user behavioral intention - Michael Reinhart Adiwinata; Husna Leila Yusran (Enrichment : Journal of Management, 2023)
Healthcare in Indonesia was going through inadequate doctor-patient ratio phenomenon which could give difficulties for some people to obtain healthcare. As technology developed and advanced, there have been alternative methods for healthcare workers to provide health services online, through telemedicine. The increased number of telemedicine users since the pandemic has required service providers to improve the quality of their services according to patient’s needs. The quality of these services could be influenced by factors such as perceived usefulness, perceived risk and offline consultation habits. This paper aims to analyze the relationship between perceived usefulness, perceived risk & offline consultation habits on user satisfaction, perceived value and behavioral intention. Data was gathered from cross-sectional design via google form. Data was analyzed using SPSS version 25 and SEM AMOS 21 program to analyze the influence between variables. The results showed that seven hypotheses were supported, and a hypothesis was not supported, where perceived risk variable had no effect on perceived value. This study shows that the variables perceived usefulness, perceived risk, offline consultation habits, perceived value and user satisfaction have significant impact on the behavioral intention to use telemedicine.